SỬ DỤNG TRÌNH TỰ NUCLEOTIDE VÙNG GEN NHÂN (ITS-rRNA) ĐỂ XÁC ĐỊNH LOÀI LAN THUỘC CHI LAN HOÀNG THẢO (DENDROBIUM) - Vũ, Đình Duy (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
USING ITS NUCLEAR GENE NUCLEOTIDE SEQUENCES FOR IDENTIFICATION SPECIES IN DENDROBIUMDNA barcoding is a useful tool for species identification using standardized genomic DNA fragments. We used DNA barcodes (Internal transcribed spacer of the nuclear ribosomal DNA - ITS-rDNA) to explore Dendrobium anosmum, and to investigate the current taxonomy of Dendrobium. In this study, the success rate for PCR of ITS region was 100%. The success rate for bidirectional sequencing of PCR product was 100% with length of 650bp. All 15 samples from two provinces (Hai Duong and Hoa Binh) of Vietnam have close relationship with D. anosmum (MLBS=97%, BPP=100%). Genetic p-distances interspecific divergence within and among Dendrobium species was varied from 1% to 17%, average (12.12%). The genetic relationship of species/gender belonging to the Dendrobium genus showed that they have the same evolutionary origin.